The collembolan fauna of Maestrazgo caves (Teruel, Spain) with description of three new species - Jordana, Rafael; Fadrique, Floren; Baquero, Enrique (Zootaxa, 2012)
Three new species of cavernicolous Collembola belonging to genera Pygmarrhopalites and Oncopodura from five cavesat El Maestrazgo (Teruel, Spain) are described: Pygmarrhopalites maestrazgoensis sp. nov., P. cantavetulae sp. nov. andOncopodura fadriquei Jordana & Baquero sp. nov. In addition five other species have been found in the same caves:Heteromurus nitidus (Templeton, 1836), Pseudosinella encrusae Gisin & Gama, 1969 (second record of the species),Megalothorax minimus Willem, 1900, Protaphorura aconae Arbea & Jordana 1994 (second record of the species), andSchaefferia decemoculata (Stach, 1939) (sensu: Thibaud 1970). The explorations of cave fauna in these cavities has beencarried out by the "Associació Catalana de Bioespeleologia” under the sponsorship of CEMAT (Centro de Estudios del Maestrazgo Turolense).